Design and performance test of a combined and adjustable precise rice seed metering device - Xu, Hongmei; Liu, Wanru; Liu, Hao; Liu, Zhangfen; Zhang, Guozhong (International Journal of Agricultural and Biological Engineering, 2025)
In order to address the issues of narrow seeding adjustment range and low accuracy of grain placement in the existing rice seeders, a mechanically and pneumatically adjustable precision hole-type seeder is designed. It is primarily composed of a seeding disk, air chamber, seed box, and seed discharge device. The design incorporates a symmetrical structure with dual disks and dual casings, enabling both single-sided and double-sided single-row and synchronized seeding. Based on theoretical analysis of seed charging, seed protection, and seed release, the following parameters were determined: seeding disk diameter of 192 mm, suction hole diameter of 1.48-1.52 mm, suction hole spacing of 3.04-9.41 mm, type hole distribution circle radius of about 62.1-77.0 mm, type hole diameter of 9 mm, stirrer plate length of 4.705-9.410 mm, and stirrer plate inclination angle of 0°-30°. Using a coupled simulation method of EDEM-Fluent, the impact of different type hole distributions, stirrer plate lengths, and inclination angles on seeding performance was analyzed. The results indicate that the main and secondary influencing factors on seed charging qualification rate are type hole diameter, stirrer plate inclination angle, and stirrer plate length. The optimal performance is achieved with a type hole diameter of 6 mm, stirrer plate length of 5 mm, and stirrer plate inclination angle of 10°, resulting in a seed charging qualification rate of 71.42%. Furthermore, Fluent software was utilized to analyze the influence of different suction hole spacings, diameters, and air chamber radii on seeding performance. The results revealed that the suction of rice seeds by the hole can be better realized with a suction hole spacing of 6 mm, a suction hole diameter of 1.5 mm, and an air chamber radius of 62 mm, at which the average negative pressure in the suction hole center was about 2824.56 Pa. A bench test and a field test were further performed on the device. The results showed that increasing the number of type holes and suction holes can contribute to more stable regulation of the seeding amount. The optimal single-sided seed metering could achieve a maximum qualified rate of 82.5%, a missing rate of 12.5%, and a repeating rate of 5%; while the optimal double-sided seed metering could obtain a maximum qualified rate, missing rate, and repeating rate of 72.5%, 15%, and 12.5%, respectively. This adjustable precision seeder can meet the requirements of precision sowing of Huanghuazhan rice varieties, and the research findings can provide reference for the structural optimization of precision rice seeders. Keywords: rice, combined seed metering device, adjustable seeding amount, EDEM-Fluent DOI: 10.25165/j.ijabe.20251801.8193 Citation: Xu H M, Liu W R, Liu H, Liu Z F, Zhang G Z. Design and performance test of a combined and adjustable precise rice seed metering device. Int J Agric & Biol Eng, 2025; 18(1): 101–114.